Burden of Congenital Rubella Syndrome (CRS) in Bangladesh: Systematic Review of Existing Literature and Transmission Modelling of Seroprevalence Studies - Chan, Jocelyn; Wu, Yue; Wood, James; Muhit, Mohammad; Mahmood, Mohammed K.; Karim, Tasneem; Moushumi, Farhana; Jones, Cheryl A.; Snelling, Tom; Khandaker, Gulam (Infectious Disorders - Drug Targets, 2020)
Background and Objectives: Congenital Rubella Syndrome (CRS) is the leading cause of vaccine-preventable congenital anomalies. Comprehensive country-level data on the burden of CRS in low and middle-income countries, such as Bangladesh, are scarce. This information is essential for assessing the impact of rubella vaccination programs. We aim to systematically review the literature on the epidemiology of CRS and estimate the burden of CRS in Bangladesh. Methods: We conducted a systematic review of existing literature and transmission modelling of seroprevalence studies to estimate the pre-vaccine period burden of CRS in Bangladesh. OVID Medline (1948 – 23 November 2016) and OVID EMBASE (1974 – 23 November 2016) were searched using a combination of the database-specific controlled vocabulary and free text terms. We used an age-stratified deterministic model to estimate the pre-vaccination burden of CRS in Bangladesh. Findings: Ten articles were identified, published between 2000 and 2014, including seven crosssectional studies, two case series and one analytical case-control study. Rubella seropositivity ranged from 47.0% to 86.0% among all age population. Rubella sero–positivity increased with age. Rubella seropositivity among women of childbearing age was 81.0% overall. The estimated incidence of CRS was 0·99 per 1,000 live births, which corresponds to approximately 3,292 CRS cases annually in Bangladesh. Conclusion: The estimated burden of CRS in Bangladesh during the pre-vaccination period was high. This will provide important baseline information to assess the impact and cost-effectiveness of routine rubella immunisation, introduced in 2012 in Bangladesh.
Keywords: CRS